Intralesional Bleomycin for the Treatment of Resistant Palmoplantar and Periungual Warts - Suchana Marahatta; Dhan Keshar Khadka; Sudha Agrawal; Arpana Rijal (Hindawi Limited, 2021)
Introduction. Periungual, palmar, and plantar warts are difficult to treat with poor treatment response. Intralesional (IL) bleomycin has shown promising results for their treatment in a few reports. However, we need further evidence before opting it for treating difficult sites and resistant warts. Hence, we conducted this study to assess the efficacy and safety of IL bleomycin for the treatment of resistant palmoplantar and periungual warts. Methods. In this retrospective study, we included all patients who were given IL bleomycin for warts over a year. Maximum three sittings of bleomycin (1 mg/ml) were given monthly, and they were followed up for 3 months after the procedure. The response was categorized as complete, near-complete, significant, moderate, mild, and no clearance for 100%, 75-99%, 50-74%, 25-49%, 1-25%, and 0% clearance, respectively. Results. Out of 29 patients, follow-up details were available only in 19 patients (53 warts). The mean duration was 2.5 ± 1.47 years. The number of past interventions ranged from 2-4. Wart clearance after the first intervention was complete in 36.84%, near-complete in 26.31%, significant in 26.31%, and moderate in 10.53%. Wart clearance after the last intervention was complete in 89.47% and near-complete in 10.52% of patients. However, during 3 months of follow-up after the last injection, 15.78% had a recurrence. None of them had severe local and systemic side effects. Conclusions. IL bleomycin could be a better treatment option for the treatment of resistant and difficult warts. However, we observed a higher recurrence rate even in a shorter follow-up. Hence, we need further studies with larger samples.